Rethinking the Academic Study of the Ulama Tradition - Zamir, Syed Rizwan (Islamic Studies, 2014)
This essay surveys the Western academic study of the ulama tradition by examining: 1) how it has evolved over the last few decades and with what results; 2) the recurrent underlying premises, trends and approaches that have set the criteria and benchmarks for the academic study of the ulama tradition; 3) the methodological questions and concerns in the study of the ulama tradition; 4) why should the ulama tradition be studied; and finally, 5) in view of the foregoing results, the possibility of an alternative conceptual model for the study of the ulama tradition, and by extension for study of contemporary Islamic intellectual life.